- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 2,678

If $f^{-1}(x)$ is the inverse of $f(x)=e^x$, then $f^{-1}(x)=$

$a. \ln\dfrac{2}{x}$

$b. \ln \dfrac{x}{2}$

$c. \dfrac{1}{2}\ln x$

$d. \sqrt{\ln x}$

$e. \ln(2-x)$

ok, it looks slam dunk but also kinda ???

my initial step was

$y=e^x$ inverse $\displaystyle x=e^y$

isolate

$\ln{x} = y$

the overleaf pdf of this project is here .... lots of placeholders...

https://drive.google.com/open?id=1WyjkfLAzhs4qF3RYOgSJrllP4hoKC5d4

$a. \ln\dfrac{2}{x}$

$b. \ln \dfrac{x}{2}$

$c. \dfrac{1}{2}\ln x$

$d. \sqrt{\ln x}$

$e. \ln(2-x)$

ok, it looks slam dunk but also kinda ???

my initial step was

$y=e^x$ inverse $\displaystyle x=e^y$

isolate

$\ln{x} = y$

the overleaf pdf of this project is here .... lots of placeholders...

https://drive.google.com/open?id=1WyjkfLAzhs4qF3RYOgSJrllP4hoKC5d4

Last edited: